Analytical study on washing machine interface design - Abushammala, Sakher J; Abdul Rahman, Julaila (Global Academic Excellence (M) Sdn. Bhd., 2018)
Washing machine plays an essential and pivotal role in our daily modern lives. Washing machine design trends have been rapidly changing since the beginning of its invention. Human evolves to lean towards fabric care and hygiene rather than “just clean”. Therefore, washing machine designs later includes technologies that support assorted washing techniques and methods. These improved designs eventually developed various interactions existing between users and products. Product interface is the medium between user and product in which transferring and exchanging information takes place. Today’s washing machine interface become complicated and packed with many unused modes and features. This contributes to the confusion of user. Therefore, this study aims to understand user preference on washing machine interface design, taking Malaysian market and Malaysian users as an example specifically in Kuala Lumpur city. The objective of this study is to analyze Malaysian user preference on current washing machine interface design. a survey is done using user centered design approach based on user experience when operating existing washing machine interface dashboard. According to Patricia Bohm et. Al. the philosophy behind a User-Centered Design is that the user knows best. Where designers should focus on users’ needs and goals they want to accomplish (Bohm, Schneidermeier, & Wolff, 2011) This study found that There are many modes, features on current washing machine that make it complicated to operate a washing machine making the interface design more complex and difficult to understand. Many modes are not used in daily lives by users. Users prefer 1 button and less modes to operate washing machine hence less steps to follow.